Interaction between Sdo1p and Btn1p in the Saccharomyces cerevisiae model for Batten disease - Vitiello, Seasson Phillips (Oxford University Press, 2010)
Juvenile Batten disease is an autosomal recessive pediatric neurodegenerative disorder caused by mutations in the CLN3 gene. The CLN3 protein primarily resides in the lysosomal membrane, but its function is unknown. We demonstrate that CLN3 interacts with SBDS, the protein mutated in Shwachman–Bodian–Diamond syndrome patients. We demonstrate that this protein–protein interaction is conserved between Btn1p and Sdo1p, the respective yeast Saccharomyces cerevisiae orthologs of CLN3 and SBDS. It was previously shown that deletion of BTN1 results in alterations in vacuolar pH and vacuolar (H(+))-ATPase (V-ATPase)-dependent H(+) transport and ATP hydrolysis. Here, we report that an SDO1 deletion strain has decreased vacuolar pH and V-ATPase-dependent H(+) transport and ATP hydrolysis. These alterations result from decreased V-ATPase subunit expression. Overexpression of BTN1 or the presence of ionophore carbonyl cyanide m-chlorophenil hydrazone (CCCP) causes decreased growth in yeast lacking SDO1. In fact, in normal cells, overexpression of BTN1 mirrors the effect of CCCP, with both resulting in increased vacuolar pH due to alterations in the coupling of V-ATPase-dependent H(+) transport and ATP hydrolysis. Thus, we propose that Sdo1p and SBDS work to regulate Btn1p and CLN3, respectively. This report highlights a novel mechanism for controlling vacuole/lysosome homeostasis by the ribosome maturation pathway that may contribute to the cellular abnormalities associated with juvenile Batten disease and Shwachman–Bodian–Diamond syndrome.